FATHER'S ROLE ON THE EXCLUSIVE BREASTFEEDING - Eka Safitri Yanti; Ayi Diah Damayani (Women, Midwives and Midwifery, 2021)
Background: Breastfeeding is a difficult time for a mother. A mother hopes that she can fully breastfeed in the first 6 months of her baby's life. But unfortunately, breastfeeding mothers often face various problems in baby care which result in disruption of breastfeeding such as stress due to not being adapted to being a mother, or due to pressure from the surrounding environment. The role of a partner is very important in helping mothers deal with problems that may arise. Father's support can help mothers, especially in their coping, in dealing with stress that may arise when breastfeeding. Purpose: The purpose of this study was to determine the father's role during the breastfeeding period to achieve the success of exclusive breastfeeding. Methods: This research method used a cross-sectional design which was carried out in Bangka Belitung Islands Province. The study was conducted on 35 married couples who have babies between 6 months to 1 year old. The aspects of the father's support that were assessed were financial, emotional, and physical. Quantitative data were analyzed using an independent t-test, while qualitative data were analyzed using chi-square. Results: The results of statistical analysis showed that there was no significant relationship between financial support (p = 0.372), emotional support (p = 0.166), and physical support (p = 0.227) on the success of exclusive breastfeeding. Although there is a close relationship if the three aspects are given together without reducing one aspect of support (p = 0.009). Conclusion: This shows that the father's support must include all three aspects, both financial, emotional, and physical to determine the success of exclusive breastfeeding. Objectives: The purpose of this study was to determine the role of breastfeeding fathers in the success of exclusive breastfeeding. Methods: This research method used a cross sectional design which was carried out in Desa Tanjung Gunung, Kabupaten Bangka Tengah, Kepulauan Bangka Belitung. The study was conducted on 35 married couples who have babies between 6 months to 1 year old. Results: The results of statistical analysis showed that there was no significant relationship between financial support (p = 0.372), emotional support (p = 0.166) and physical support (p = 0.227) on the success of exclusive breastfeeding. Although there is a close relationship if the three aspects are given together without reducing one aspect of support (p = 0.009). Conclusion: This shows that the father's support must include all three aspects, both financial, emotional and physical to determine the success of exclusive breastfeeding..